Caffeine ingestion enhances repetition velocity in resistance exercise: a randomized, crossover, double-blind study involving control and placebo conditions - Grgic, J.; Venier, S.; Schoenfeld, B. J.; Mikulic, P. (Journal of Human Kinetics, 2020)
We aimed to examine the effects of placebo and caffeine compared to a control condition on mean velocity in the bench press exercise. Twenty-five resistance-trained men participated in this randomized, crossover, double-blind study. The participants performed the bench press with loads of 50%, 75%, and 90% of one-repetition maximum (1RM), after no supplementation (i.e., control), and after ingesting caffeine (6 mg/kg), and placebo (6 mg/kg of dextrose). At 50% 1RM, there was a significant effect of caffeine on mean velocity compared to control (effect size [ES] = 0.29; p = 0.003), but not when compared to placebo (ES = 0.09; p = 0.478). At 75% 1RM, there was a significant effect of caffeine on mean velocity compared to placebo (ES = 0.34; p = 0.001), and compared to control (ES = 0.32; p < 0.001). At 90% 1RM, there was a significant effect of caffeine on mean velocity compared to placebo (ES = 0.36; p < 0.001), and compared to control (ES = 0.46; p < 0.001). There was no significant difference between placebo and control in any of the analyzed outcomes. When evaluated pre-exercise and post-exercise, 20% to 44% and 28% to 52% of all participants identified caffeine and placebo trials beyond random chance, respectively. Given that the blinding of the participants was generally effective, and that there were no significant ergogenic effects of placebo ingestion, the improvements in performance following caffeine ingestion can be mainly attributed to caffeine`s physiological mechanisms of action.